2015
DOI: 10.1111/zsc.12155
|View full text |Cite
|
Sign up to set email alerts
|

Integrative taxonomy of the Italian pine voles,Microtus saviigroup (Cricetidae,Arvicolinae)

Abstract: The Italian endemic voles belonging to the Microtus savii group (de Sélys‐Longchamps, 1838) include five controversial taxa, namely M. savii savii, M. s. niethammericus Contoli ; M. s. tolfetanus Contoli , M. s. nebrodensis (Minà‐Palumbo, 1868) and M. brachycercus (Lehamann, 1961). A previous mtDNA phylogenetic analysis revealed three main mtDNA lineages that do not correspond to the recognized taxa. Here, we perform a comprehensive univariate and multivariate analysis of craniodental measurements in 151 speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…However, mtDNA hapotypes belonging to this species showed that its northernmost limit is much further to the north in central Italy (Fig. 3) , Bezerra et al 2016. Its species status is supported by chromosomal and hybridological data (Galleni et al 1994).…”
Section: Endemic Speciesmentioning
confidence: 68%
See 1 more Smart Citation
“…However, mtDNA hapotypes belonging to this species showed that its northernmost limit is much further to the north in central Italy (Fig. 3) , Bezerra et al 2016. Its species status is supported by chromosomal and hybridological data (Galleni et al 1994).…”
Section: Endemic Speciesmentioning
confidence: 68%
“…It seems to be missing from the slopes of Etna. Castiglia et al (2008) suggested a possible specific status of the Sicilian Microtus, then they confirmed this in further papers based on molecular genetics, karyotypic and morphological studies (Gornung et al 2011, Bezerra et al 2016. The split of this species with the other species of the complex, M. savii and M. brachycercus, dated about 1.81 million years ago (MYA) (Tougard 2017).…”
Section: Endemic Speciesmentioning
confidence: 72%
“…; Bezerra et al. ). The cluster of M. gerbei with the clade formed by M. lusitanicus and M. duodecimcostatus is also highly supported, as in Robovský et al.…”
Section: Discussionmentioning
confidence: 97%
“…Considering the criteria for mammal species recognition, specifically the level of Cytb divergence (>5%, Baker & Bradley, ; >1.5%–2.5%, Tobe, Kitchener, & Linacre, ), on the basis of current data, it is best to consider these genera as monotypic. Moreover, while FGB has been proven to vary between species of mammals (e.g., Bezerra et al., ), and especially in Carnivora (e.g., Veron, Patou, Tóth, Goonatilake, & Jennings, ; Veron et al., 2015), it showed no or very little variation among Galidiinae genera.…”
Section: Discussionmentioning
confidence: 99%